Tyr78Phe Transthyretin Mutation with Predominant Motor Neuropathy as the Initial Presentation - Giulietta Riboldi; Roberto Del Bo; Michela Ranieri; Francesca Magri; Monica Sciacco; Maurizio Moggio; Nereo Bresolin; Stefania Corti; Giacomo P. Comi (Case Reports in Neurology, 2011)
Transthyretin (TTR) amyloidosis, the most frequent form of hereditary amyloidosis, is caused by dominant mutations in the TTR gene. More than 100 mutations have been identified. Clinical manifestations of TTR amyloidosis are usually induced by extracellular amyloid deposition in several organs. The major neurological manifestation is motor-sensory neuropathy associated with dysautonomic impairment. Here, we describe a63-year-old man who came to our institution due to a suspected motor neuron disease. During a 4-year follow-up period, he underwent extensive clinical examination, electromyographic studies, sural nerve biopsy and TTR gene analysis by direct sequencing. Despite the predominant motor involvement, the detailed clinical examination also showed some mild sensory and dysautonomic signs. In addition, his clinical and family history included multiorgan disorders, such as carpal tunnel syndrome, as well as conditions with cardiac, renal, eye, and hepatic involvement. The sural nerve biopsy disclosed amyloid deposition, and the sequence analysis of the TTR gene detected a heterozygous Tyr78Phe substitution. The TTR gene variant found in our patient had only been described once so far, in a French man of Italian origin presenting with late-onset peripheral neuropathy and bilateral carpal tunnel syndrome. The predominant motor involvement presented by our patient is an uncommon occurrence and demonstrates the clinical heterogeneity of TTR amyloidosis.